Serotype distribution, clinical characteristics, and antimicrobial resistance of pediatric invasive pneumococcal disease in Colombia during PCV10 mass vaccination (2017–2022) - Camacho-Moreno, Germán; Leal, Aura Lucia; Patiño-Niño, Jaime; Vasquez-Hoyos, Pablo; Gutiérrez, Ivan; Beltrán, Sandra; Álvarez-Olmos, Martha I.; Mariño, Ana-Cristina; Londoño-Ruiz, Juan Pablo; Barrero, Rocio; Rojas, Juan Pablo; Espinosa, Fabio; et al. (Frontiers in Medicine, 2024)
Introduction: Invasive Pneumococcal Disease(IPD) causes significant morbidity and mortality in children under 5y. Colombia introduced PCV10 vaccination in 2012, and the Neumocolombia network has been monitoring IPD in pediatric patients since 2008. Materials and methods: This study is a secondary analysis of a prospective cohort involving pediatric patients with IPD admitted to 17 hospitals in Colombia, from January 1st, 2017, to December 31st, 2022. We present data on serotypes(Spn), clinical characteristics, and resistance patterns Results: We report 530 patients, 215(40.5%) were younger than 24 months. Among these, 344 cases(64.7%) presented with pneumonia, 95(17.9%) with primary bacteremia, 53(10%) with meningitis, 6(1.1%) had pneumonia and meningitis, and 32(6%) had other IPD diagnosis. The median hospital stay was 12 days (RIQ 8-14 days), and 268(50.6%) were admitted to the ICU, of whom 60(11,3%) died. Serotyping was performed in 298(56.1%). The most frequent serotypes were Spn19A (51.3%), Spn6C(7.7%), Spn3 (6.7%), Spn6A (3.6%), and Spn14 (3.6%). Of 495(93%) isolates with known susceptibility, 46(9.2%) were meningeal(M) and 449(90.7%) non-meningeal(NM). Among M isolates, 41.3% showed resistance to penicillin, and 21.7% decreased susceptibility to ceftriaxone. For NM isolates, 28.2% had decreased susceptibility to penicilin, and 24.2% decreased susceptibility to ceftriaxone. Spn19A showed the highest resistant to penicillin at 47% and was linked to multiresistance. Conclusion: The prevalence of PCV10-included serotypes decreased, while serotypes 19A and 6C increased, with Spn19A being associated with multiresistance. These findings had played a crucial role in the decision made by Colombia to modify its immunization schedule by switching to PCV13 in July 2022.